Industrial Efficiency and State Intervention - Tomlinson, Jim; Tiratsoo, Nick (Taylor and Francis, 1993)
Nick Tiratsoo and Jim Tomlinson describe and assess the Labour Party's development of a policy of improving industrial efficiency. They concentrate on the debates and initiatives of the wartime period and subsequent implementation of policy under Attlee. The book modifies existing historiography in two ways - it shows that the Labour Party of 1945-51 was concerned mainly with industrial modernization, not with creating the Welfare State, and it tackles the consequently necessary re-evaluation of wider theories about Britain's economic decline